Performance comparison of multicell series and npc multilevel сonverters for a statcom - Belakehal, S.; Djellad, A.; Chenni, R. (Національний технічний університет "Харківський політехнічний інститут", 2019)
Abstract. In this paper, we present a comparative study of the performances of the multicells series and the Neutral-Point-Clamped (NPC) three-level converters used at synchronous staticcompensators (STATCOM) for the control of the voltage at a point of the network. The analysis consists on a mathematical modeling, a pulse width modulation (PWM) control algorithm application and a simulation using the Matlab Simulink environment. The simulation results obtained show that the STATCOM allows the regulation of the voltage at the point of common coupling (PCC) by acting the reactive energy that it can supply or absorb.

В статье представлено сравнительное исследование характеристик многоэлементных последовательных и трехуровневых преобразователей со связанной нейтральной точкой, используемых в синхронных статических компенсаторах (STATCOM) для управления напряжением в точке сети. Анализ основан на математическом моделировании, алгоритме управления с широтно-импульсной модуляцией (ШИМ) и моделировании с использованием среды Matlab Simulink. Полученные результаты моделирования показывают, что STATCOM позволяет регулировать напряжение в точке общей связи действием реактивной энергии, которую он способен подавать или поглощать.
Keywords: VSC; NPC converter; multicell series converter; modeling; преобразователь источника напряжения; преобразователь со связанной нейтральной точкой; многоэлементный последовательный преобразователь; моделирование